Degree of Sustainability Maturity SME’s Based on Demographic and Spirituality - I Putu Deddy Samtika Putra; I Putu Fery Karyada; Ni Komang Sumadi; I Wayan Budi Satria; Rai Dwi Andayani W. (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2026)
This study aims to analyze the level of sustainability maturity of micro, small, and medium enterprises (MSMEs) based on demographic characteristics and spirituality. The research employed an online survey method involving 414 MSME owners in Bali, with hypothesis testing conducted using Analysis of Variance (ANOVA). The findings indicate that there are significant differences in sustainability maturity levels across business categories, income levels, and eco-spirituality. These results suggest that both demographic factors and spiritual dimensions play an important role in shaping sustainability orientation and practices among MSMEs. This study contributes original value by being among the first to measure MSME sustainability maturity through the integration of demographic and spirituality-based factors.